2021
DOI: 10.18502/ijps.v16i3.6251
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Group Hope Therapy Training on the Quality of Life and Meaning of Life in Patients with Multiple Sclerosis and Their Family Caregivers

Abstract: Objective: Multiple sclerosis is a chronic, progressive neurological disease that, due to its special nature, has various physical and mental influences on the patients and their family's lives, decreasing the quality of life and threatening the meaning of life. The purpose of the present study was to evaluate the effectiveness of the group hope therapy training on the quality and the meaning of life in patients with multiple sclerosis and their family caregivers. Method: This quasi-experimental study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…38 Another study showed that the meaning of life in the patients with MS and the caregivers increased significantly after group hope therapy training. 39…”
Section: Religion Spirituality and Spiritual Care For Patients With Msmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Another study showed that the meaning of life in the patients with MS and the caregivers increased significantly after group hope therapy training. 39…”
Section: Religion Spirituality and Spiritual Care For Patients With Msmentioning
confidence: 99%
“…38 Another study showed that the meaning of life in the patients with MS and the caregivers increased significantly after group hope therapy training. 39 In our clinic practice, we have seen the positive effects of religion and spirituality on the psychosocial, mental, and spiritual health of patients with many neurological patients including MS patients. Second, many patients and caregivers have found spiritual peace, consolation, and relief when they read the book entitled "Message for the Sick" 40 written by Bediüzzaman Said Nursi (1877Nursi ( -1960.…”
Section: Spirituality Is Nourished and Strengthened By Religionmentioning
confidence: 99%
“…40 Studies show that individuals with strong spiritual beliefs, who are in connection with stable spiritual sources can better endure and cope with marital problems. 41 , 42 They also generally show less friction in their family relationships and in dealing with everyday problems. On the contrary, grown-up children of families with low sense of spirituality were reported to exhibit more instances of shirking from responsibility and keeping low profile during crises when family members need support.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy implies a positive cognitive reconstruction of a challenging situation. Interventions focused on re-evaluating goals and values have been demonstrated to support meaningfulness and well-being in caregivers [41]. In the same direction, religious coping has been associated with PTG by re-evaluating despairing situations into challenging assignments.…”
Section: Influence Of Post-traumatic Growth and Mental Health On Copi...mentioning
confidence: 99%